2021
DOI: 10.1108/ilt-01-2021-0026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dynamic characteristics of spiral groove liquid film seal under thermal–fluid–solid coupling

Abstract: Purpose The purpose of this paper is to investigate the dynamic characteristics of spiral groove liquid film seal under the effect of thermal–fluid–solid coupling. Design/methodology/approach The dynamic analysis model of spiral groove liquid film seal under the effect of thermal–fluid–solid coupling was established by perturbation method. The steady-state and perturbation Reynolds equations were solved, and the steady-state sealing performance and dynamic characteristic coefficients of the liquid film were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Assuming convection at the boundary between the fluid film and the solid (based on the principle of energy conservation), the two-dimensional energy equation in the fluid film can be established as follows [23,24]:…”
Section: Thermal Analysis In Fluid Filmmentioning
confidence: 99%
“…Assuming convection at the boundary between the fluid film and the solid (based on the principle of energy conservation), the two-dimensional energy equation in the fluid film can be established as follows [23,24]:…”
Section: Thermal Analysis In Fluid Filmmentioning
confidence: 99%
“…Substituting the equations (4) and (5) into equations (1)–(3), the perturbation Reynolds equation considering cavitation is obtained as follows 29,30 : Substituting the perturbation in z , x and y direction into equation (6), the perturbation Reynolds equations considering cavitation in z , x and y direction are obtained as follows: …”
Section: Theoretical Modelmentioning
confidence: 99%
“…where p kj (k = z, α, β; j = i, r,) are the perturbation pressure in z, x and y direction. Substituting the equations ( 4) and ( 5) into equations ( 1)-( 3), the perturbation Reynolds equation considering cavitation is obtained as follows 29,30 :…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Jiang et al (2019Jiang et al ( , 2020 improved the stability of dry gas seals by enhancing the film stiffness via the surface textures. Yu et al (2021) indicated that the stability of spiral groove seals can be enhanced by thermoplastic deformation. Hao et al (2018) and Yang et al (2016) conducted research on the dynamic characteristics of spiral groove seals with different groove structures, surface topographies and working conditions.…”
Section: Introductionmentioning
confidence: 99%